A Statistical Analysis of the Influences of Multi-Timescale Waves on Tropical Cyclone Sudden Track Changes Over the Western North Pacific - Bi, Xinxin; Chen, Guanghua; Shi, Donglei; Wang, Ke; Zhou, Weican (Frontiers in Earth Science, 2020)
This study investigates the potential impacts of multi-timescale atmospheric modes on tropical cyclone (TC) abrupt track turnings over the western North Pacific during the period of 2000–2019. The composite large-scale environmental flow patterns of the sudden right-turning (SRT) and left-turning (SLT) TCs show that the SRT process is generally accompanied by the continuous deepening westerly trough, the weakening and eastward retreat of subtropical high favoring the strengthening of the asymmetric southwesterly around TC center, while the SLT cases are mainly steered by the stronger easterlies to the north which are attributed to the increased pressure meridional gradient. Furthermore, the TCs with sudden track changes are divided into 5 categories according to the quantitative contribution of wave modes. The composite analyses indicate that: (1) The synoptic-scale wave poses influence on most of the SRT cases through a southeast-northwest-oriented wave train to the northeast of the TC, inducing the prominent southerly flows in the vicinity of TC center. (2) The intra-seasonal oscillation (ISO) pattern for the SRT cases is characterized by a southeast-northwest-oriented circulation dipole, and the TCs embedded between the two dipole components are impacted by the strengthened southwesterly anomalies. In contrast, the SLT events are located in the northwest of a zonally-elongated cyclonic ISO circulation, which enhances the northeasterly flows for the sharply left turning. (3) The SRT cases dominated by the basic background flow are situated in the western flank of a broad anticyclonic circulation and subject to the northward steering flow anomalies, while for the SLT cases, the left track turning is mainly induced by the uniform easterly trade winds at the lower latitudes.